Freedom Redefined: Tagore’s Poetic Vision in the Age of Globalization and Digital Surveillance - Abhijit Deb (ILN Journal: Indian Literary Narratives, 2025)
Rabindranath Tagore’s poems “Where the Mind is Without Fear” and “Freedom” interrogate freedom not merely as political independence but as a radical reimagining of human consciousness. While rooted in the anti-colonial context, these poems critique dogma, fear, and intellectual inertia as deeper forms of bondage. This study employs a dual methodology of textual analysis and socio-historical contextualization to interpret Tagore’s conception of freedom within both colonial and contemporary frameworks. Drawing on postcolonial theory, globalization studies, and digital humanism, it explores how Tagore’s poetic ideals challenge both imperial domination and modern structures of control. In the contemporary landscape of globalization and digital surveillance, Tagore’s vision acquires renewed urgency by exposing how technology-driven control and cultural homogenization replicate colonial subjugation in subtler forms. The study reveals that “Where the Mind is Without Fear” envisions a society grounded in fearless reasoning and moral clarity, while “Freedom” expresses a prophetic plea for liberation from ignorance, conformity, and mechanization. Tagore’s poetics thus function as a counter-discourse demanding critical thought, moral courage, and emancipatory education, sustaining relevance in resisting authoritarianism, disinformation, and ethical erosion. His work embodies a timeless critique of unfreedom in its shifting historical manifestations, redefining liberty as an ongoing process of ethical awakening and intellectual renewal. In an age marked by digital dependency and socio-political inequality, Tagore’s call for fearless minds and truthful living continues to offer a powerful framework for preserving human dignity and justice.